Political Institutions and Government Spending Behavior: Theory and Evidence from Iran - Sajjad Faraji Dizaji; Mohammad Reza Farzanegan; Alireza Naghavi (Center for Economic Studies and ifo Institute (CESifo), 2015)
This study examines how the quality of political institutions affects the distribution of the government budget in Iran. We first introduce a mechanism through which democracy can shift government expenditure from national defense (military) to productivity-enhancing public spending (e.g., education). Using impulse response functions (IRF) and a variance decomposition analysis (VDC) on the basis of a vector autoregressive (VAR) model, our results imply that the response of military spending to an improvement (a deterioration) of democratic institutions is negative (positive) and statistically significant, whereas that of education spending is positive (negative) and significant. Our results are robust to other indicators of political institutions, different orderings of variables in the VAR and alternative specifications of government spending categories.
Keywords: H11; H41; P16; O53; O43; 330; political institutions; military spending; education spending; Iran; VAR modeling